Fenomena Phubbing di Kalangan Remaja dan Dampaknya terhadap Society 5.0 - Haidir Rahmad; Tri Wahyu Ramadhan; Muhammad Dhany Fazar Ilahi; Surawan Surawan (Jurnal Pendidikan Agama Islam, 2026)
The phenomenon of phubbing, which describes the behavior of ignoring others in favor of using digital devices, has become a serious concern in today’s digital era. This paper explores the background, consequences, and influence of phubbing on college students and adolescents, particularly in the context of Society 5.0 which emphasizes the integration of technology in daily life. Using a literature review method, this article presents a holistic analysis of the factors that influence phubbing, its impact on social and academic well-being, and the challenges and strategies in addressing this phenomenon. Conclusions emphasize the need for comprehensive and coordinated efforts to reduce the prevalence of phubbing and promote responsible and balanced use of technology among college students and adolescents